Financial Sector Assessment Program : Montenegro Finance for Growth - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
This technical note reviews with the status access to finance for enterprises in Montenegro, identifies key bottlenecks, and provides recommendations on how to address main challenges. In particular, the note focuses on SME finance by assessing (i) bank SME lending, and (ii) current constraints facing further development and deepening of the non-bank credit sector. The note develops key findings presented to the authorities during the FSAP mission and summarized in the aide-mémoire. The Montenegrin financial sector has yet to recover from the collapse of the real estate bubble in 2008. The crisis has exposed important weaknesses in the financial sector’s governance, oversight and infrastructure which had fueled years of unsustainable credit growth leading up to the crisis. The resulting balance sheet deleveraging and restructuring process has reduced the banking sectors’ ability to finance the corporate sector, which continues to suffer from slow economic growth and remaining weaknesses in the business environment.